1987
DOI: 10.1016/0304-4165(87)90155-3
|View full text |Cite
|
Sign up to set email alerts
|

The relative contributions of vitamin E, urate, ascorbate and proteins to the total peroxyl radical-trapping antioxidant activity of human blood plasma

Abstract: The relative contributions of vitamin E, urate, ascorbate and proteins to the total peroxyl radical-trapping antioxidant activity of human blood plasma Wayner, D. D. M.; Burton, G.W.; Ingold, K. U.; Barclay, L. R. C.; Locke, S. J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
392
7
19

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 824 publications
(436 citation statements)
references
References 37 publications
18
392
7
19
Order By: Relevance
“…Thus, it is suggested that the resistance of cord plasma to Cu 2 -mediated lipid peroxidation observed in the current study is at least partly due to circulating levels of urate, albumin, bilirubin and sulphydryl groups. Urate is a powerful hydrophilic antioxidant and is a scavenger of singlet oxygen (Ames et al, 1981) and peroxyl radicals (Wayner et al, 1987). Urate can also act as a plasma antioxidant by binding transition metal ions (Becker, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is suggested that the resistance of cord plasma to Cu 2 -mediated lipid peroxidation observed in the current study is at least partly due to circulating levels of urate, albumin, bilirubin and sulphydryl groups. Urate is a powerful hydrophilic antioxidant and is a scavenger of singlet oxygen (Ames et al, 1981) and peroxyl radicals (Wayner et al, 1987). Urate can also act as a plasma antioxidant by binding transition metal ions (Becker, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma sulphydryl groups are thought to represent the ®rst line of defence against peroxyl radicals, and the most expendable source of antioxidants in plasma, as there is no known mechanism of regeneration once they are oxidised (Wayner et al, 1987). Sonani et al, (1994) found that albumin and sulphydryl proteins were prominent in scavenging carbon-centred free radicals under anaerobic conditions in plasma, where ascorbate, vitamin E and nonsulphydryl amino acids were ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several plasma components will Plasma total homocysteine, oxidative damage and antioxidant activity SJ Moat et al contribute to this activity including uric acid, albumin, thiols and a-tocopherol (Miller et al, 1993). Plasma thiols have been shown to contribute to various measures of antioxidant activity Miller et al, 1993;Wayner et al, 1987) and there may have been changes in the redox state of plasma thiols following a reduction in plasma total homocysteine. There is current interest in the potential antioxidant role for folate, but a doubling in plasma folate was associated with such a small increase in TAOC that it is unlikely that there is a direct causative association.…”
Section: Effect On Antioxidant Activitymentioning
confidence: 99%
“…Again, lipid peroxidation is a free radical-mediated oxidative deterioration of polyunsaturated fatty acid residues in membrane lipids, resulting in the formation of lipid hydroperoxide (Wayner et al, 1987) [36]. Malondial-dehydes, the peroxidative end product of unsaturated fatty acids, are water soluble; when they are free they could dissipate from erythrocyte into the plasma (Jain, 1988) [37].…”
Section: Discussionmentioning
confidence: 99%